Kontribusi Pemikiran Hadis Rashīd Ridhā - Abustani Ilyas (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2007)
This writing discusses the contribution of the laissez-faire of Rashīd Ridā’s ḥadīth, which includes the historicity of ḥadīth. According to him, the first ḥadīth writer was Khālid bin Mi’dān al-Himsī, a tabi’in in the 1st century A.H., not al-Zuhrī. The authority of ḥadīth, as a general rule in religion, is considered to be the Qur’an and mutawatir amaliyyah ḥadīth. The emphasized authenticity aspect of the ḥadīth in terms of sanad is to avoid excessive fanaticism in a madhhab. From the aspect of matan, he rejects ḥadīth containing strange elements, such as ḥadīth about signs of the Day of Judgment, Dajjal, the Mahdi of the end times, the descent of the Prophet Isa (Jesus), and others. He also uses contextual and interstitial interpretation, believing in understanding the ḥadīth along with its relevance to the social conditions of the Prophet Muhammad, returning its meaning to the Qur’an.